Opportunities to improve fisheries management through innovative technology and advanced data systems. Issue 3 (13th March 2019) - Bradley, Darcy; Merrifield, Matt; Miller, Karly M.; Lomonico, Serena; Wilson, Jono R.; Gleason, Mary G.
Abstract: Fishery‐dependent data are integral to sustainable fisheries management. A paucity of fishery data leads to uncertainty about stock status, which may compromise and threaten the economic and food security of the users dependent upon that stock and increase the chances of overfishing. Recent developments in the technology available to collect, manage and analyse fishery‐relevant data provide a suite of possible solutions to update and modernize fisheries data systems and greatly expand data collection and analysis. Yet, despite the proliferation of relevant consumer technology, integration of technologically advanced data systems into fisheries management remains the exception rather than the rule. In this study, we describe the current status, challenges and future directions of high‐tech data systems in fisheries management in order to understand what has limited their adoption. By reviewing the application of fishery‐dependent data technology in multiple fisheries sectors globally, we show that innovation is stagnating as a result of lack of trust and cooperation between fishers and managers. We propose a solution based on a transdisciplinary approach to fishery management that emphasizes the need for collaborative problem‐solving among stakeholders. In our proposed system, data feedbacks are a key component to effective fishery data systems, ensuring that fishers and managers collect, have access to and benefit from fisheries data as they work towards a mutually agreed‐upon goal. A new approach to fisheries data systems will promote innovation to increase data coverage, accuracy and resolution, while reducing costs and allowing adaptive, responsive, near real‐time management decision‐making to improve fisheries outcomes.